2018
DOI: 10.1038/s41598-018-19538-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic recruitment of ubiquitin to mutant huntingtin inclusion bodies

Abstract: Many neurodegenerative diseases, such as Huntington’s disease, are hallmarked by the formation of intracellular inclusion bodies (IBs) that are decorated with ubiquitin, proteasomes and chaperones. The apparent enrichment of ubiquitin and components involved in protein quality control at IBs suggests local ubiquitin-dependent enzymatic activity. In this study, we examine recruitment of ubiquitin to IBs of polyglutamine-expanded huntingtin fragments (mHtt) by using synthesized TAMRA-labeled ubiquitin moieties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 49 publications
5
25
0
Order By: Relevance
“…Recent examples of delivery methods of proteins include the use of endosomolytic peptides, [12,13] poly(disulfide)s, [14] microinjection, [15] electroporation, [16] small-molecule additives, [17] bioreversible esterification, [18] and modifying the target protein with cell-penetrating peptides (CPPs). Recent examples of delivery methods of proteins include the use of endosomolytic peptides, [12,13] poly(disulfide)s, [14] microinjection, [15] electroporation, [16] small-molecule additives, [17] bioreversible esterification, [18] and modifying the target protein with cell-penetrating peptides (CPPs).…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples of delivery methods of proteins include the use of endosomolytic peptides, [12,13] poly(disulfide)s, [14] microinjection, [15] electroporation, [16] small-molecule additives, [17] bioreversible esterification, [18] and modifying the target protein with cell-penetrating peptides (CPPs). Recent examples of delivery methods of proteins include the use of endosomolytic peptides, [12,13] poly(disulfide)s, [14] microinjection, [15] electroporation, [16] small-molecule additives, [17] bioreversible esterification, [18] and modifying the target protein with cell-penetrating peptides (CPPs).…”
Section: Introductionmentioning
confidence: 99%
“…This can be visualized by SDS-PAGE WB after lysing cells and solubilizing the insoluble fraction including aggregated mHtt ( Figure 3D). FRAP experiments showed that TAMRA-Ub was reversibly recruited to mHtt IBs, which was prevented when either E1 ligase or DUB inhibitors were used (Juenemann et al, 2018). This indicates that (de)ubiquitinating enzymes recruited to IBs are involved in mHtt ubiquitination as well as of other proteins sequestered into IBs, resulting in ongoing ubiquitination and deubiquitination of proteins present in IBs with reversible recruitment of ubiquitin.…”
Section: Studying the Dynamics Of Htt Aggregate Ubiquitination Ubiquimentioning
confidence: 98%
“…Upon electroporation, TAMRA-Ub is mainly present in the nucleus and on cytoplasmic vesicles, but when mHtt induced IBs are present most TAMRA-Ub is recruited to IBs (Figure 3C). Both TAMRA-Ub and endogenous Ub are present in the entire mHtt aggregates, including the inner core, and TAMRA-Ub was incorporated into Ub linkages including poly-ubiquitinated mHtt itself (Juenemann et al, 2018). This can be visualized by SDS-PAGE WB after lysing cells and solubilizing the insoluble fraction including aggregated mHtt ( Figure 3D).…”
Section: Studying the Dynamics Of Htt Aggregate Ubiquitination Ubiquimentioning
confidence: 99%
See 1 more Smart Citation
“…To study synthetic proteins in the native environment, new protein delivery methods are constantly being developed. Recent examples of delivery methods of proteins include the use of endosomolytic peptides, poly(disulfide)’s, microinjection, electroporation, small‐molecule additives, bioreversible esterification, and modifying the target protein with cell‐penetrating peptides (CPPs) . Notably, only a few studies have attempted the delivery of synthetic and semisynthetic proteins that are uniquely modified .…”
Section: Introductionmentioning
confidence: 99%